KERAGAAN PRODUKSI SUSU DAN EFISIENSI USAHA PETERNAKAN SAPI PERAH RAKYAT DI INDONESIA - Alla Asmara; Yeti Lis Purnamadewi; Deni Lubis (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The main issue in the dairy farm business managed by the communities is the relatively low efficiency level of the businesses run by some of the farmers. The research objectives were to analyze the performance of dairy farm business, factors that influence dairy production, and technical efficiency level of the community dairy farm businesses in Indonesia. The research was conducted by surveys so that the primary data from the samples of farmers’ households were obtained through interviews and questionnaires. The analytical method used in this study was the stochastic frontier production function. The results of the analysis showed that the number of the lactating cows raised in small-scaled farm businesses decreased from the previous year; on the other hand, the number of the lactating cows in large-scaled farm businesses increased. Meanwhile, the average milk productions have declined in both small and large-scaled farm businesses. The results of the analysis of the stochastic frontier production function showed that forage fodder input (HMT), concentrates, employment and number of lactating cows are influential factors on milk production.Thus, the efficiency analysis suggests that the level of technical efficiency of large-scaled farm businesses is higher than that of the small-scaled farm businesses, while the efficiency distribution is predominantly in the range of 0,80 to 1,00, which means that most farm businesses have achieved a high level of technical efficiency. The individual factors from the farmers which are influential in decreasing business inefficiency include age and education level; on the contrary, the influences of experience and ownership of the garden affect the efficiency in the opposite way. Keywords: technical efficiency, production function, frontier stochastic, dairy